Žiniasklaida užsienio kalbomis Lietuvoje: ką renkasi vartotojai - Nevinskaitė, Laima (Information & Media, 2009)
Straipsnyje pateikiama žiniasklaidos užsienio kalbomis pasirinkimo tarp Lietuvos didmiesčių gyventojų lietuvių analizė, atlikta remiantis reprezentatyvios šių miestų gyventojų apklausos duomenimis. Daugiausiai dėmesio skiriama žiniasklaidos rusų ir anglų kalbomis pasirinkimo analizei: kaip dažnai mokantys rusų ir (ar) anglų kalbas renkasi žiniasklaidą šiomis kalbomis, kaip šie pasirinkimai yra pasiskirstę tarp amžiaus grupių, koks žiniasklaidos užsienio kalbomis vartojimo dažnumas, palyginti su kitomis kalbų vartojimo sritimis. Remiantis skirtingais teoriniais požiūriais į kalbos ir tapatybės santykį, žiniasklaidos užsienio kalbomis vartojimą galima vertinti dvejopai: kaip kultūrinės, lingvistinės ir politinės įtakos šaltinį arba tiesiog vartotojo galimybių rinktis jo poreikius tenkinantį žiniasklaidos turinį išplėtimą.Pagrindiniai žodžiai: žiniasklaidos vartojimas, žiniasklaida užsienio kalbomis, globalizacija.Media in Foreign Languages in Lithuania: Consumer ChoicesLaima NevinskaitėSummaryThe author analyses the use of media in foreign languages, mostly Russian and English, among Lithuanians living in the main cities of Lithuania (Vilnius, Kaunas and Klaipeda). The analysis is based on data of a representative survey on the knowledge of languages and their use in these cities, performed within the research project “Cities and Languages” by Vilnius Universit).The use of media in foreign languages is important in several respects, which are discussed in the article. First, it can be regarded as a source of cultural and linguistic influence within the context of cultural and linguistic globalisation. In Lithuania and in other former Soviet Union states, media in Russian are also treated as a potential source of political influence. Second, it is important in respect of media market, since foreign media can be regarded as a source of a wider content choice for media consumer.Results of the analysis have shown that a significant part of Lithuanians (up to 40 per cent) frequently use media in foreign languages, although the number of frequent users still lags behind the amount of those who use the media in Lithuanian. The data show a wider knowledge of Russian and generally a wider use of mass media in Russian. Russian is used more often than English as a language for listening radio and watching TV; the use of printed media (books and periodicals) in Russian is higher, but close to that in English; English is much wider used as a language of the internet use. The trends are clearly more positive for English, since it is more popular among young people, even among those who know Russian as well. The article includes a further analysis of media choices among those who know the languages in question, these choices among the age groups, and the frequency of media use in foreign languages in comparison to the use of those languages in other domains.